Teaching Graduate Career Classes: A National Survey of Career Instructors. (December 2013) - Osborn, Debra S.; Dames, Levette S.
<x xml:space="preserve">Abstract</x> Ninety‐one instructors reported their attitudes toward teaching a master's‐level career development course. The participants represented counseling programs in 41 states. The areas of focus included the theories taught, activities and assignments used, course evaluation processes, and advice the participants would offer to other instructors. Implications for counselor education and directions for future research are also discussed.